Watching bonds move in a large antiaromatic ring - Peeks, M; Anderson, H (Cell Press, 2019)
In antiaromatic molecules, single and double bonds interconvert via a process called bond-shift valence tautomerization, which is often so fast that its rate is difficult to measure experimentally. In this issue of Chem, Wu and co-workers use dynamic NMR spectroscopy to study valence tautomerization in a giant antiaromatic macrocycle.